2015
DOI: 10.1021/acschemneuro.5b00192
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Seeding Interaction between β-Amyloid and Human Islet Amyloid Polypeptide

Abstract: Alzheimer's disease (AD) and type 2 diabetes (T2D) are two common protein misfolding diseases. Increasing evidence suggests that these two diseases may be correlated with each other via cross-sequence interactions between β-amyloid peptide (Aβ) associated with AD and human islet amyloid polypeptide (hIAPP) associated with T2D. However, little is known about how these two peptides work and how they interact with each other to induce amyloidogenesis. In this work, we study the effect of cross-sequence interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
83
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 62 publications
9
83
0
1
Order By: Relevance
“…As a control, for the pure Aβ 1-42 peptides incubated at 25 µΜ, ThT profile showed a typical nucleation-polymerization aggregation profiles, consisting of a very short lag phase of 1 h, a rapid growth phase between 2-7 h, and a final equilibrium phase after 7 h, where the final ThT fluorescence intensity reflects the amount of fibrillar material formed. Since pure Aβ at 25 µM experienced rapid aggregation at the early stage, lag phase only existed for a very short time period (~1 h), consistent with our previous works 12, 36,45 . In Fig.…”
Section: Hp-β-cd Inhibits Aβ42 Fibrillizationsupporting
confidence: 90%
See 1 more Smart Citation
“…As a control, for the pure Aβ 1-42 peptides incubated at 25 µΜ, ThT profile showed a typical nucleation-polymerization aggregation profiles, consisting of a very short lag phase of 1 h, a rapid growth phase between 2-7 h, and a final equilibrium phase after 7 h, where the final ThT fluorescence intensity reflects the amount of fibrillar material formed. Since pure Aβ at 25 µM experienced rapid aggregation at the early stage, lag phase only existed for a very short time period (~1 h), consistent with our previous works 12, 36,45 . In Fig.…”
Section: Hp-β-cd Inhibits Aβ42 Fibrillizationsupporting
confidence: 90%
“…To prevent reinventing the wheel, we proposed to search the existing drug database for other diseases to identify potential Aβ inhibitors. Since pure Aβ at 25 µM experienced rapid aggregation at the early stage, lag phase only existed for a very short time period (~1 h), consistent with our previous works 12, 36,45 . Experimental data showed that HP-β-CD were not only nontoxic to cells, but also greatly inhibited Aβ fibrillation and reduced Aβ-induced toxicity in a concentration-dependent manner.…”
supporting
confidence: 90%
“…Centrifuge the Aβ-hIAPP mixture solution at 13,148 × g for 30 min at 4 °C to remove any potential oligomers, followed by extracting 90% of the top Aβ-hIAPP solution (1.8 mL) in the monomeric state of both peptides for cross-seeding tests [23] (Fig 2). …”
Section: Methodsmentioning
confidence: 99%
“…In vitro, l'hété-ronucléation d'Ab par d'autres protéines amyloïdes telles que la caséine, l'a-synucléine (impliquée dans la maladie de Parkinson) ou des dépôts amyloïdes des îlots de Langerhans pancréatiques (« Islet Amyloid Protein » (IAPP, s'accumulant dans le diabète de type II)) a été montrée (O'Nuallain et al 2004;Ono et al 2014;Hu et al 2015). Les données in vivo sont plus contradictoires.…”
Section: Risques D'ensemencement Par Des Hétéronucléantsunclassified